Development of an improved dental porcelain on the basis of flow materials from Thailand - Sawangwan N. (2014)
Dental porcelain is a special type of ceramic with high glassy phase content used for the restoration of teeth. In general, this porcelain type is insoluble in oral fluids, has high wear resistance, and excellent colour matching as required for aesthetic dental porcelain restoration. The fracture toughness for dental porcelain should amount to 1.49-1.76 Mpa·m0.5. The purpose of these investigations was to find the appropriate composition as well as processing and sintering conditions for dental porcelain on the basis of raw material from Thailand. The results show that a material could be developed with enough high compressive strength of about 240 N/mm2, high hardness of 0.647 GPa, and a higher fracture toughness of 2.46 MPa·m0.5 than other commercial materials. Essentially, the selection of optimal conditions for the technological manufacturing process could also be achieved.